Maximizing digitalization to maintain consumer loyalty - I'tisham, Muhammad; Chusniyah, Tutut; Hakim, Shaqilla (Association for Scientific Computing Electrical and Engineering, 2024)
In the digital era, mobile applications have become essential tools for companies to foster consumer loyalty by enabling seamless interactions, efficient transactions, and accessible customer service. This study examines the impact of digitalization on customer loyalty through a qualitative case study of Sociolla, focusing on the SOCO application. Data were collected via purposive sampling involving a company representative and a Sociolla consumer and analyzed using thematic analysis, presenting findings narratively. Sociolla demonstrates the strategic use of digital platforms for branding and consumer engagement. The consumer informant reported increased interest, enthusiastic event participation, app downloads, and a clear understanding of Sociolla’s brand identity, highlighting the ecosystem fostered between the company and its customers. These findings underscore the broader applicability of effective digital strategies in engaging customers and enhancing brand loyalty across industries. The study concludes that mobile applications capture customer attention, drive active involvement, and strengthen brand relationships when effectively leveraged. It also identifies a need for future research to quantitatively assess the impact of digital platforms on loyalty, engagement, and brand attachment. However, the study's scope is limited to Sociolla, a cosmetics retail brand with a predominantly female customer base. Expanding research to include diverse demographics, regions, and industries could provide richer insights into the effectiveness of digitalization strategies in maintaining customer loyalty across varied contexts